PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS KEARIFAN LOKAL SEBAGAI SUMBER BELAJAR LINGKUNGAN PESISIR - Husain, Zakaria; Nusantari, Elya; Sidik Katili, Abubakar; Hamidun Susanti, Marini; Mustaqimah , Nur (Jurnal Biogenerasi, 2025)
This study aims to describe the development of an interactive e-module that integrates local wisdom as a learning resource in the coastal environment. The main objective is to help students gain a more meaningful and contextual understanding of coastal ecosystems, while increasing their active involvement in the learning process. This study uses a Research and Development approach with the ADDIE development model. Limited trials were conducted on 26 grade X students at SMA Negeri 2 Tilamuta. Data collection techniques include observation, interviews, questionnaires, and documentation. The research instruments consisted of a needs analysis sheet, validation sheets from material and media experts, and assessment tools from practitioners to evaluate the feasibility of the e-module. The results showed that the interactive e-module received a very positive response in the practicality test, with a percentage of teacher responses of 88% (very good), students of 95% (very good), the implementation of learning 1 of 92% (very good), and learning 2 of 88% (very good). These findings indicate that interactive e-modules based on local wisdom are a feasible and innovative alternative learning resource for use in the classroom..